Occurrence, potential sources and ecological risk estimation of microplastic towards coastal and estuarine zones in Malaysia - Zainuddin, Azim Haziq; Aris, Ahmad Zaharin; Mohd Zaki, Muhammad Rozaimi; Md. Yusoff, Fatimah; Wee, Sze Yee (Elsevier, 2022)
Extensive global plastic production has led to microplastic (MP) pollution of marine ecosystems. This study analysed the abundance of MPs in the surface water of tropical coastal and estuarine zones in Malaysia affected by rapid urbanisation and intense human activity. It also estimated the risk posed by MPs to the marine environment. Mean MP abundance ranged from 2.10 to 6.80 particles/L. Fourier-transform infrared spectroscopic analysis found that the MP polymers were dominated by cellophane (54%), followed by polyester (33%) and polyethylene (2%). The risk posed by MPs was estimated with the risk quotient (RQ) method which found no potential ecological risk to both coastal and estuarine areas (RQ < 1). This study will serve as a baseline for future monitoring of MP pollution of marine water to assess the impact of heavily urbanised coastal and estuarine zones.